Fabrication and characterization of Cu2O, ZnO and ITO thin films toward oxide thin film solar cell by mist chemical vapor deposition method. Issue 7 (31st March 2014) - Ikenoue, Takumi; Sakamoto, Shin‐ichi; Inui, Yoshitaka
Abstract: N‐type zinc oxide (ZnO) and p‐type cuprous oxide (Cu2 O) thin films were fabricated by an ultrasonic spray‐assisted mist chemical vapor deposition (mist CVD) method. The films of transparent conductive gallium‐doped ZnO (ZnO:Ga) and indium tin oxide (ITO) were also formed by the same technique. ZnO thin films have showed n‐type conductivity with carrier concentration of 3.6 × 10 19 cm –3 and mobility of 8.6 cm 2 /V·s. Cu2 O thin films showed p‐type conductivity whose carrier density and mobility were 3.3 × 10 15 cm –3 and 0.20 cm 2 /V·s, respectively. ZnO:Ga and ITO thin films have high transmittance over 85% in visible region and low resistivity values of 2.3 × 10 –3 and 1.4 × 10 –4 Ω·cm, respectively. These properties are suitable for transparent electrodes of solar cells. The results encourage the successive fabrication by the same process technique of solar cell structure, that is, the multilayer structure of ITO (or conductive ZnO), n‐ZnO, and p‐Cu2 O films on a glass substrate. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)